investigation on bacterial causes of infants upper respiratory tract infections in El-Gabal Alakhdar region-Libya - Abdelkafe, Azza S.; El-Ghareeb, K.A.; Nasib, Muftah A. (Al-Mukhtar Journal of Sciences, 2009)
Acute and chronic respiratory tract infections are an important health problems among young and adult ages, and have serious impact on economy in many countries. This study was performad to isolate and identify the bacterial causes of upper respiratory tract diseases in infants using standard biochemical and microbiological techniques. The study involved (180) patients suffering from tonsillitis and pharyngitis (95), sinusitis (62) and chronic otitis media (23) collected(110) cases from males and (70) cases were from females and their age from one year up to 5 years. Our results showed that incidence of respiratory diseases increased through the first three years of life where it was (22.5%), (20.0%) and (21.3%) respectively. and then decreaseds at four and five years of age (18.6%) and(17.5%) respectively, and incidence of infection was higher in males (61.1%) than females (38.9%). In this study (80) bacterial strains were obtained from the (180) cases by incidence of (44%).. In case of tonsillitis and pharyngitis (38) bacterial isolates were recovered by incidence of(47.5%), followed by 20 bacterial isolates from cases of sinusitis (25%), and 22 bacterial isolates from chronic otitis media (27.5%). In general our finding revealed that the most common bacteria causing upper respiratory tract infections in infants were Staph.aureus (31.3%) followed by Proteus spp. and E.coli (16.3%) for each, klebsiella spp. (8.8%) and P.aeruginosa (5%). With respect to antibiotic sensitivity of bacterial isolates results showed that Gram positive cocci Staphylococcus aureus and Streptococcus pyogenes were (84100%) Sensitive to Amikacin , Gentamicin, Cefalexin , Ampicillin and Cefotaxime Sensitivity to Ofloxacin , and Rifampicin.